2018
DOI: 10.1136/archdischild-2017-313801
|View full text |Cite
|
Sign up to set email alerts
|

Children and young people’s versus parents’ responses in an English national inpatient survey

Abstract: ObjectiveDespite growing interest in children and young people’s (CYP) perspectives on healthcare, they continue to be excluded from many patient experience surveys. This study investigated the feasibility of, and additional information gained by, measuring CYP experiences of a recent hospital admission.DesignCross-sectional analysis of national survey data.SettingInpatients aged 8–15 years in eligible National Health Service hospitals, July–September 2014.Participants6204 parents/carers completed the parent s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
50
1

Year Published

2018
2018
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(53 citation statements)
references
References 12 publications
2
50
1
Order By: Relevance
“…The results of this dyad analysis agree with the parent-child dyad research across other health care professions, concluding that there are low levels of agreement between parents and children. 30 This shows the need to have both parties involved when questioning or consistently using the same group, either parents or children, when it pertains to determining the specialization level of a youth athlete. 16,17,30,31 Knowing the specialization level of an athlete can better equip clinicians to address sport specialization.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The results of this dyad analysis agree with the parent-child dyad research across other health care professions, concluding that there are low levels of agreement between parents and children. 30 This shows the need to have both parties involved when questioning or consistently using the same group, either parents or children, when it pertains to determining the specialization level of a youth athlete. 16,17,30,31 Knowing the specialization level of an athlete can better equip clinicians to address sport specialization.…”
Section: Discussionmentioning
confidence: 99%
“…30 This shows the need to have both parties involved when questioning or consistently using the same group, either parents or children, when it pertains to determining the specialization level of a youth athlete. 16,17,30,31 Knowing the specialization level of an athlete can better equip clinicians to address sport specialization. Future research is encouraged to further understand the lack of agreement between parent-child and its impact on participation behaviors, performance outcomes, and psychosocial experiences.…”
Section: Discussionmentioning
confidence: 99%
“…This highlights both the importance of publishing age-specific mortality rates, and the need for wider outcome measures that reflect long-term prognosis and quality of life, including resilience and attainment of lifelong goals. Similarly, although patient experience and patient-centredness of care have historically received much less attention for CYP than adults, and may need to be measured differently, CYP have the right to have their voice heard,10 24 they provide information which cannot be gleaned from other sources,25 and they consistently rate feeling listened to as their most important care priority from the age of 8 onwards 26…”
Section: Key Concepts In Quality and Measurementmentioning
confidence: 99%
“…The guiding principle of their institute is that 'Everybody deserves high quality healthcare, and that understanding the nature of people's needs and preferences is integral to providing a high level of care' [3]. Children and adolescents form a distinct patient group, whose needs and preferences have been relatively under-represented in published research [4,5]. In recognition of this, the Picker Institute assisted in developing the first evidence-based patient-reported experience measure [6] and conducting the first children's national UK survey in a decade [3,7].…”
Section: Introductionmentioning
confidence: 99%
“…The nurse, while attempting to empty his catheter bag, rejected Kelvin's experience and needs by imposing her own experience onto him [1]. While HCPs and parents act as an essential source of support and advocacy, research has shown that their experiences are an inadequate proxy for children's and adolescents' experiences [5,17], and that children and adolescents are best placed to describe their own experiences and needs [18,19].…”
Section: Introductionmentioning
confidence: 99%